Public opinions on the implementation of free public Wi-Fi in Malawi - Frank Makoza (ZBW – Leibniz Information Centre for Economics, 2024)
Free public Wi-Fi is perceived to be one of the solutions of addressing barriers of Internet adoption in Malawi. The Government of Malawi received funding from the World Bank to implement 32 hotspots of free public Wi-Fi across the country. This paper analysed the stakeholder's opinions regarding the implementation of free public Wi-Fi program. The study used a qualitative research approach. Data was collected from government department websites, social media platforms and online news websites. The data was analysed using content analysis. The findings showed positive and negative views from stakeholders on the free public Wi-Fi program. The positive opinions were related to promoting digital inclusion, safety health practices, supporting collaboration and improving education activities. The negative opinions were related to politics, biases in selection of locations, poor quality of services, priority of the program and sustainability of the program. The study offers useful insights on investment, appropriation and operations as factors that can affect free public Wi-Fi implementation in the context of developing countries.
Keywords: 320; Free public Wi-Fi; Online media; Public opinions; Internet; Digital inclusion; Malawi